2010
DOI: 10.1176/appi.ps.61.3.317
|View full text |Cite
|
Sign up to set email alerts
|

The Schizophrenia Care Management Program for Family Caregivers of Chinese Patients With Schizophrenia

Abstract: This is the Pre-Published Version.2 Objectives: This study tested the effectiveness of a schizophrenia care management program for family caregivers of Chinese patients with schizophrenia in Hong Kong.Methods: A multisite controlled trial was conducted with 92 patient-caregiver dyads. They were randomly assigned to either the schizophrenia care management program or to usual care. The patients' symptoms, functioning, and length of rehospitalization and their families' perceived social support, expressed emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…A few controlled trials (Chien et al, 2008, Glynn et al, 2006, Wiedemann, 2003 have suggested that family-led mutual support groups can improve family functioning and caregiving through two mechanisms: (a) increased social support and, in turn, an enhanced experiential knowledge and sense of control over interpersonal and caregiving skills; and (b) an "all in the same boat" belief, with better sharing and the adoption of effective strategies in patient care among group members. Similar to the findings in this trial, a few studies conducted in Hong Kong (Chien et al, 2006, Chien et al, 2008, Chien and Lee, 2010 suggest that family mutual support groups for Chinese people with severe mental illness are effective in offering practical assistance and advice on caregiving and in improving the willingness of people to share their caregiving experiences openly with other families, particularly when little help is forthcoming from elsewhere.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A few controlled trials (Chien et al, 2008, Glynn et al, 2006, Wiedemann, 2003 have suggested that family-led mutual support groups can improve family functioning and caregiving through two mechanisms: (a) increased social support and, in turn, an enhanced experiential knowledge and sense of control over interpersonal and caregiving skills; and (b) an "all in the same boat" belief, with better sharing and the adoption of effective strategies in patient care among group members. Similar to the findings in this trial, a few studies conducted in Hong Kong (Chien et al, 2006, Chien et al, 2008, Chien and Lee, 2010 suggest that family mutual support groups for Chinese people with severe mental illness are effective in offering practical assistance and advice on caregiving and in improving the willingness of people to share their caregiving experiences openly with other families, particularly when little help is forthcoming from elsewhere.…”
Section: Discussionsupporting
confidence: 79%
“…They may also find it difficult to build trust and rapport with the family therapist (Fung and Ma, 1997). Chien and Lee (2010) have suggested that although Chinese families are often the ones most in need of intervention, they seldom seek help from health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…7 Social support has also been linked to outcome in schizophrenia and related disorders, either directly 8 or through the impact of family-related interventions on symptoms, 9 relapse, 10 social functioning, 9 as well as the number and length of hospitalizations. [11][12][13] Further, numerous studies reveal the positive impact of social support and the quality of social networks on remission status, 14 improvement of symptoms, rates of hospitalization, 15 and the degree of adaptive functioning. 16 It is possible that the relation between social support and outcome is, at least partly, mediated through the effect of social-especially family-support on adherence to medication.…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, family therapy has proven effective in providing knowledge enhancement about mental illness and its treatment and consequently may offer a better ability to cope with the patients and their disease. [29][30][31][32] Thorup et al compared integrated treatment and standard treatment in 547 patients experiencing a first episode of psychosis. 33 The integrated treatment focused on social skills, information about the pharmacological therapy, its side effects, and relapse prevention.…”
Section: Fit and Integrated Treatmentmentioning
confidence: 99%